THE COMPUTER GRAB HOLDING CONTROL SYSTEM ON A GSU (GRAB SHIP UNLOADER) CRANE: THE COMPUTER GRAB HOLDING CONTROL SYSTEM ON A GSU (GRAB SHIP UNLOADER) CRANE - Alimuddin Alimuddin2 (Universitas Negeri Jakarta, 2025)
Grab Ship Unloader (GSU) is one of the main pieces of equipment in bulk material handling operations at industrial ports, where the reliability of the control system plays a crucial role in ensuring operational efficiency and safety. One of the critical subsystems in a GSU is the grab holding control system, which regulates the opening, holding, and closing processes of the grab during material handling. This internship report aims to analyze the grab holding control system of the GSU crane at PT Krakatau Bandar Samudra, with a particular focus on the Programmable Logic Controller (PLC)-based control logic and the implementation of ladder diagrams. The research methods include direct field observation, literature review, and discussions with field supervisors and academic advisors. The analysis focuses on the operating principles of the control system, operating modes (manual, automatic, and high-speed), safety interlocks, and the utilization of sensors such as encoders, load cells, and motor torque feedback. The results indicate that the grab holding control system is designed with a well-structured logic that processes position and torque signals to determine safe and stable hold, close, and open commands. The PLC ladder diagram plays a significant role in managing automatic cycles, speed control through ramp steps, and preventing motion conflicts. With this control system, grab operations on the GSU crane can be carried out more precisely, efficiently, and safely. This internship report is expected to serve as a reference for the development, maintenance, and improvement of GSU crane control systems in industrial port environments.